Psalm structures. - Raabe, Paul R., 1953- (Library of Hebrew Bible/Old Testament studies., 1990)
This study identifies and describes the basic building blocks of a biblical psalm: the levels of colon, verse, strophe and stanza. In this study eleven psalms have been chosen with stanzas that are clearly demarcated by the presence of refrains. Seven of these are analysed thoroughly (Psalms 42-43, 46, 49, 56, 57, 59) and another four more briefly (Psalms 39, 67, 80, 99). This is a timely and closely argued statement of the importance of integrating structure and content in one''s interpretation of a psalm.